Given:
[tex]x=-\dfrac{8}{9},\ y=-\dfrac{3}{5}[/tex]
To verify:
[tex]x+y=y+x[/tex]
Solution:
We need to verify,
[tex]x+y=y+x[/tex]
Taking left hand side, we get
[tex]LHS=x+y[/tex]
After substituting the values, we get
[tex]LHS=-\dfrac{8}{9}+\left(-\dfrac{3}{5}\right)[/tex]
[tex]LHS=-\dfrac{8}{9}-\dfrac{3}{5}[/tex]
[tex]LHS=\dfrac{-40-27}{45}[/tex]
[tex]LHS=\dfrac{-67}{45}[/tex]
Now,
Taking right hand side, we get
[tex]RHS=y+x[/tex]
After substituting the values, we get
[tex]RHS=-\dfrac{3}{5}+\left(-\dfrac{8}{9}\right)[/tex]
[tex]RHS=-\dfrac{3}{5}-\dfrac{8}{9}[/tex]
[tex]RHS=\dfrac{-27-40}{45}[/tex]
[tex]RHS=\dfrac{-67}{45}[/tex]
Clearly,
[tex]LHS=RHS[/tex]
Hence verified.